Medium-term immunogenicity of three doses of BNT162b2 and CoronaVac in Hong Kong neuromuscular disease patients - Michael Kwan Leung Yu; Sophelia Hoi Shan Chan; Daniel Leung; Samuel Cheng; Leo Chi Hang Tsang; Tsz Chun Kwan; Kaiyue Zhang; Xiwei Wang; Wenwei Tu; Malik Peiris; Yu Lung Lau; Jaime S. Rosa Duque (Taylor & Francis Group, 2024)
The durability of the immunogenicity elicited by three doses of mRNA-based BNT162b2 and whole-virus inactivated CoronaVac in patients with neuromuscular diseases, particularly those on immunosuppressive drugs and variants of concern, has not been well-established. Our goal was to evaluate medium-term humoral immunogenicity outcomes after 3 doses of these vaccines. Peripheral blood samples were collected from participants 14-49 days and 155-210 days after administration of the third vaccine dose to assess humoral immune responses through serological assays. The immunogenicity outcomes of each patient were compared to those of three age-matched healthy control participants, ensuring a balanced comparison. Both patients that received 3 doses of BNT162b2 and 10 (90.9%) patients that received CoronaVac seroconverted against wild-type-SARS-CoV-2 virus, showing comparable antibody responses to healthy participants. After 6 months, one patient in BNT162b2 and all four patients in CoronaVac groups maintained seropositivity. The JN-1 specific binding antibody response was lower compared to wild-type virus. The use of corticosteroids did not affect seroconversion rate against wild-type virus or JN.1 variant. BNT162b2 and CoronaVac were immunogenic for neuromuscular diseases patients, maintaining durability after 6 months even for those on corticosteroids. Our data support a rapid immunization series utilizing mRNA-based and whole-virus inactivated vaccines for future pandemic.